A preliminary study on the effects of rice water on capsicum annum L. plant growth / Muhammad, N. A. ... [et al.] - N. A., Muhammad; S. N. A., Abdullah; N. N., Rodzali; S. N., Hashim (2020)
In Malaysia, chilies are intensively used in the food industry, mainly as a dipping sauce and food preparation. Synthetic fertilizers are commonly used to boost the production of chilies to fulfill market demands. However, synthetic fertilizers have a long-term impact on the environment. Alternatively, natural fertilizers such as rice water and animal wastes provide a better solution compared to commercial fertilizers. Rice water was traditionally used as one of the methods to promote plant growth. However, there is a lack of scientific evidence to prove rice water potential as natural fertilizers to date. Therefore, this study aims to determine the effect of rice water on chili plant growth. In this study, the plant was watered with rice water twice a day and was placed directly under sunlight within seven weeks. The final height of the plants was compared with the control and chili plant with synthetic fertilizers. Hence, this study revealed that plant watered with rice water gives the highest growth rate (58%), control (39%), and synthetic fertilizers (49%). It can be concluded that rice water is suitable to substitute synthetic fertilizers, as it is safe, costeffective, and environmentally friendly.